The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1128/iai.56.8.2109-2113.1988
|View full text |Cite
|
Sign up to set email alerts
|

Induction of immunity with avirulent Listeria monocytogenes 19113 depends on bacterial replication

Abstract: Events necessary for triggering the cell-mediated response to intracellular parasites are poorly understood. Here we show that extremely high doses of avirulent Listeria monocytogenes 19113 (>109) induce a modest and short-lived state of resistance in BALB/c mice. Induction of this protective state could not be achieved with nonviable bacteria and was blocked by inhibiting replication of viable L. monocytogenes 19113 through antibiotic treatment. The immune response was antigen specific and could be adoptively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…All lectin-unreactive strains proved to be avirulent, and all the strains behaving as virulent in vitro – which included all clinical isolates – showed the lectin-reactive phenotype. This phenotype, however, was also displayed by four nonhaemolytic strains and by a minority of haemolytic strains behaving as avirulent in vitro , including the well-known avirulent strain NCTC 5105 (Baldridge et al ., 1988; Pine et al ., 1991). This suggests that among Listeria isolates lectin reactivity is necessarily associated with, but insufficient for, pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All lectin-unreactive strains proved to be avirulent, and all the strains behaving as virulent in vitro – which included all clinical isolates – showed the lectin-reactive phenotype. This phenotype, however, was also displayed by four nonhaemolytic strains and by a minority of haemolytic strains behaving as avirulent in vitro , including the well-known avirulent strain NCTC 5105 (Baldridge et al ., 1988; Pine et al ., 1991). This suggests that among Listeria isolates lectin reactivity is necessarily associated with, but insufficient for, pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“… ║ Carrying erm C-mediated, transferable erythromycin resistance (Roberts et al ., 1996). ❡ Avirulent strain (Baldridge et al ., 1988; Pine et al ., 1991). # Associated with a case of meningitis (Anonymous, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…The question arises as to what these protective antigens might be. Numer-ous immunization studies performed previously with non-pathogenic Listeria have demonstrated their inability to generate long-lasting protection [13][14][15]. Also, mice infected with listeriolysinnegative strains do not acquire resistance because such bacteria are rapidly eliminated from the infected host even if repeated doses at regular intervals were administered to mice [16].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13]27 Skin disorders are also commonly seen in association with HIV infection, being diagnosed in more than 90% of infected patients during the course of the disease. [28][29][30][31] In Ethiopia, approximately 800,000 people living with HIV/ AIDS, with important implications for virus circulation. Skin manifestations may represent, in many cases, the alert sign of an underlying HIV infection and/or progression to AIDS and might thus help in formulating a diagnostic suspicion, particularly in resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%